APPLICATION OF INTENSIVE LIGHT RADIATION IN THE PATIENT WITH ERYTHEMATOTELANGIECTATIC ROSACEA - T. A. Gaydina; P. A. Skripkina; A. O. Galayda; E. G. Dvornikova; E. I. Kaletnik; E. V. Dontsova (SINAPS LLC, 2018)
We present a description of the clinical case of a patient with an erythematotelangiectatic type of rosacea. Rosacea is a chronic recurrent dermatosis, characterized by skin lesions of the face in the  form of erythema and papulopustular elements, which has  polyethological origin. The disease occurs more frequently in women  aged 30-50 years who have a certain genetic predisposition to  transient reddening of the skin of the face or less often of the neck  and the decollete zone. It is believed that the dermatosis is more  likely to affect the I and II phototypes, but the disease can occur in  any skin phototype. The patient came to the clinic with complaints  about rashes in the chin and nasolabial triangle, flushing of the face,  accompanied by tingling and burning. The patient turned to the clinic with complaints about rashes in the chin and nasolabial triangle,  flushing of the face, accompanied by tingling and burning. She never consulted a dermatologist before. A diagnosis was made: "erythematotelangiectatic type of rosacea" (according to the  classification proposed by the USA National Rosacea Society, stage I  - persistent erythema and telangiectasia). Using the scale of diagnostic evaluation of rosacea, it was evaluated at 12 points.  There are many approaches to the treatment of rosacea. Drug  therapy is divided into systemic, external and complex. Systemic therapy has a number of side effects, so for light and medium-to- severe rosacea, only external therapy is more often prescribed.  Because of the presence of pathologically altered vessels, the low  efficacy of metronidazole, the patient was assigned a course of  phototherapy with intense incoherent pulsating light at standard  parameters. There was a significant improvement after two  procedures, but vessels smaller than 0.4 mm remained intact, so the duration of the first pulse was increased in order to influence small- caliber vessels. Individual selection of parameters (duration of the first impulse and fluence) was made based on the dermatoscopic picture and patient's phototype, which resulted in a significant  clinical effect and persistent remission. Using the scale of diagnostic  evaluation of rosacea it was evaluated at 1 point after treatment.  This clinical case demonstrates the effectiveness of phototherapy  with intense incoherent pulsating light with individual selection of the duration of the first pulse and energy density in patients with  erythematotelangiectatic rosacea. In IPL-treatment schemes, it is  desirable to select individual parameters for the duration of the first pulse and the energy density, based on the features of the dermatoscopic picture and skin phototype of each individual patient.